Effect of Chlamydia diagnosis on heterosexual relationships. (September 2013) - O'Farrell, Nigel; Weiss, Helen A
This study investigated whether a Chlamydia diagnosis was associated with relationship breakup or physical violence from partners when compared to other attenders at a sexually transmitted infections (STIs) clinic. Patients diagnosed with Chlamydia and who had a regular partner at the time of diagnosis, were contacted 3–12 months later and completed a questionnaire on relationship history. A comparison group of gender-matched non-STI patients were also interviewed. About half of Chlamydia cases (exposed) and non-cases (unexposed) had broken up with their partner since diagnosis (52% vs. 47%; p  = 0.42), but cases were more likely to have split up within one week of diagnosis (48% vs. 24%; p  = 0.003), and somewhat more likely to resume the relationship (24% vs. 15%; p  = 0.24). The prevalence of reported physical violence in the past year was slightly higher in cases than the unexposed group (9% vs. 4%; p  = 0.09). Cases that saw a health adviser were less likely to report experiencing physical violence than those who had not seen a health adviser (7% vs. 12%: p  = 0.31). Patients with Chlamydia are more likely to suffer relationship breakup soon after diagnosis than STI clinic attenders without an STI. Health advice should include reassurance about sexual relationships as well as safer sex.